Healthcare delivery and stakeholder's satisfaction under social health insurance schemes in India: An evaluation of Central Government Health Scheme (CGHS) and Ex-servicemen Contributory Health Scheme (ECHS) - Sukumar Vellakkal; Shikha Juyal; Ali Mehdi (Indian Council for Research on International Economic Relations (ICRIER), 2010)
This study attempted to evaluate the working of the Central Government Health Scheme (CGHS) and Ex-servicemen Contributory Health Scheme (ECHS) by assessing patient satisfaction as well as the issues and concerns of empanelled private healthcare providers. The study is based on a primary survey of 1,204 CGHS and 640 ECHS principal beneficiaries, 100 empanelled private healthcare providers and 100 officials of the schemes across 12 Indian cities. We have found that patients are reasonably well satisfied with the healthcare services of both empanelled private healthcare providers and the dispensaries-polyclinics but are relatively more satisfied with the former than the latter. We also found that beneficiaries are willing to pay more for better quality services. Though the schemes provide comprehensive healthcare services, the beneficiaries incur some out-ofpocket health expenditure while seeking healthcare. Furthermore, beneficiaries are not in favour of the recent proposal to replace the schemes with health insurance for several reasons. The empanelled private healthcare providers are dissatisfied with the terms and conditions of empanelment, especially the low tariffs for their services as compared to prevailing market rates and the delays in reimbursements from the schemes. We suggest that appropriate efforts be undertaken to enhance the quality of healthcare service provided in the dispensaries-polyclinics of the CGHS and ECHS as well as to address the issues and concerns of empanelled private healthcare providers to ensure better healthcare delivery and for a long-term, sustainable public-private partnership.
Keywords: H30; H51; H53; I19; 330; CGHS; ECHS; patient satisfaction; willingness to pay; empanelled private healthcare providers; Gesundheitsversorgung; Kundenzufriedenheit; Zahlungsbereitschaftsanalyse; Indien